ANALISIS DETERMINAN TINGKAT PENGANGGURAN TERBUKA DI INDONESIA TAHUN 2017 - 2022 - rosyid, baharudin; Moh. Athoillah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The existence of the Covid 19 pandemic in 2020 has a significant impact on the global economy and also Indonesia. One of the impacts is the increase in the unemployment rate. The GRDP growth rate is often used as an indicator in analysing the unemployment rate where when the GRDP growth rate increases, it will have an impact on reducing the unemployment rate, but in this case the increase in GRDP growth before and after the pandemic is not balanced by a decrease in the unemployment rate which is actually higher than before the pandemic. The unemployment rate can also be influenced by many factors such as UMP, Investment and Inflation. Therefore, the purpose of this study is to determine how much influence these factors have on the open unemployment rate in 34 provinces in Indonesia in 2017-2022. Using the panel data regression analysis method with the selected model, namely the fixed effect model, the results of this study show that GRDP, UMP and Inflation have a significant negative effect on the open unemployment rate, Covid 19 has a significant positive effect on the open unemployment rate, while Investment has an insignificant negative effect on the open unemployment rate.